GE_GERICHTE P/18429/2017 vom 24. Mai 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;ABUS D'AUTORITÉ;LOI FÉDÉRALE SUR LA POURSUITE POUR DETTES ET LA FAILLITE;DESSEIN | cpp.319; cp.312; LP.269